GETTING BOILER FUELS FROM LIGNITE BY PYROLYSIS - Kozhevnikov, Y.; Chizhikov, A.; Chirkov, V.; Schekochikhin, Y.; Aladinskaya, O.; Abramov, A. (Енергетика і автоматика, 2016)
Experimental studies on preparation of heavy fuel oils from lignites (Orenburg Region) by thermal decomposition method with the use of conveyor type pyrolysis plant designed by the Experimental Factory “Aleksandrovsky” (Vladimir Region) and FGBNU VIESH have been carried out. The liquid, light-brown, fraction yield was 30 % to 40 %. The calorific value of the liquid fraction was estimated to be 30MJ/kg to 35MJ/kg, and it was easy to inflame which makes it usable as a liquid burner fuel or in form of blends with heavy fuel oils or home heating oils including diesel oil.